Occurrence of the snowy grouper, Hyporthodus niveatus (Valenciennes, 1828), in Argentine waters - Trobbiani, Gastón Andres (2013)
The presence of H. niveatus in Argentina is an addition to other tropical or warm-temperate fish species where the distributional range is expanded to include higher latitudes (Galvan et al., 2005; Irigoyen et al., 2005; Scenna et al.,2006; Venerus et al., 2007; Gongora et al., 2009; Delpiani et al., 2011; Milessi et al., 2012). However, we cannot overlook the possibility that the newly-cited species had been previously unnoticed due to: (i) morphological similarities with local species and other newly described specimens; (ii) scarcity of earlier systematic studies of fish communities in the area and the fact that most distributional ranges for the Argentine marine fish fauna were described according to offshore trawling data (Venerus et al., 2007). The increasing number of fishes reported southward of previous limits contrasts records for the opposite direction; Figueroa et al. (2005) and Gonzalez-Castro et al. (2013) suggest that the new records indicate true southward expansions of warmtemperate species favored by a possible increase in water temperature. In the same way it can also be argued that many of the recently published southernmost reef-fish records are highly attached to refuges, such as serranids and pinguipedids (e.g. Irigoyen et al., 2005; Venerus et al., 2007) becoming more frequent beyond their previous known ranges. These records include more than one specimen (e.g. Irigoyen et al., 2005; this report). Such events were previously more commonly known from pelagic fish that could show exceptional migrations (e.g. Delpiani et al., 2011). However, this hypothesis cannot be convincingly evaluated because of a lack of historical data series on trends in temperature variations or shifts in other environmental variables. The absence of historical data on reef fish assemblage in the area complicates any causal assessment of these observations (Galvan et al., 2005).